Educational Objectives for Children in The Qur'an (Thematic Interpretation Approach) - Raden Fadli Daulay; Asnil Aidah Ritonga (Universitas Pahlawan Tuanku Tambusai, 2022)
Education is a planned activity, in which there are various components, so that learning must have a goal to be achieved. The Qur'an gives significant attention to learning, one of which is the purpose of education in the Qur'an when viewed from the goals, uses, and tasks of humans themselves so that the authors formulate educational goals as follows: (1) The purpose of education is to seek the pleasure of Allah (2) Ubudiyah, this goal is to deliver humans as servants who worship the Creator only to serve Allah. (3) The purpose of education is to be devoted to Allah. (4) The purpose of education as caliph fi al-Ardh, the purpose of education is also in this section must be able to carry out the mission to prosper the earth or become a leader on earth.